Organogénesis del sistema digestivo del pez Pterophylum scalare(Perciformes: Cichlidae) - Ávila Botello, Mireya (2008)
There is little knowledge on the development of the angelfish Pterophyllum scalare (Liechtenstein 1823), a spe-cies of economical and biological value for inland water ecosystems. We recorded net development time of each organogenetic stage, cumulative time and characteristic structure differentiation for each stage. We found eight organogenetic stages for the digestive system, between the gastrula and the total re-adsorption of the vitelin sack. The total time for the organogenetic development of the digestive system was 119 hours and 44 minutes.